Application of a CFD and prescribed wake model to high advance ratio wind tunnel test validation - Sugiura, M.; Tanabe, Y.; Sugawara, H.; Chopra, I. (My University, 2015)
High speed rotorcraft such as compound, co-axial helicopter and tilt-rotor has been proposed to overcome the flight speed limit of a conventional helicopter. As the design of this high speed rotorcraft proceeds, design tools such as aeromechanics analysis at high advance ratios will be necessary. A hybrid method of CFD and prescribed wake model (HCP) is one of the promising analysis tools. This HCP reduces computational cost by computing only around a blade in CFD, and wake region is computed by prescribed wake model. In this paper, it is validated with the high advance ratio wind tunnel test in the University of Maryland in terms of airload. As a result, an existing HCP shows reasonable results compared with the test data and the comprehensive analysis code UMARC. In addition to that, HCP captures the flow separation from the trailing edge around the blade root area by virtue of using CFD.
Keywords: Aerodynamics